Pengaruh Kedisiplinan, Kompetensi Terhadap Kinerja Guru Pada Sekolah Dasar Negeri Wilayah III Kecamatan Mambi di Sulawesi Barat - Rahmawati; Andi Nuryadin; Andi Irwan (STIM-LPI Makassar, 2023)
The purpose of this study was to find out and analyze the effect of discipline on teacher performance in the Region III Public Elementary School in the Mambi District in West Sulawesi, to find out and analyze the influence of competence on Teacher Performance in the Region III State Elementary School in the Mambi District in West Sulawesi, to find out and analyze which variable has the most dominant influence on teacher performance in Region III Public Elementary Schools in the Mambi District in West Sulawesi. The population in this study were all teachers, both civil servants and non-PNS, in the State Elementary School Region III, Mambi District, West Sulawesi, totaling 120 people in 2022 which included (23 people in 004 Public Elementary School, 22 012 State Elementary Schools , State Elementary School 009 totaled 24 people, Elementary School 002 totaled 23 people and 006 Public Elementary School totaled 25 people. The results showed that Discipline had a positive and significant effect on teacher performance, while competence had a positive but not significant effect on teacher performance in Region III Public Elementary Schools, Mambi District, West Sulawesi.